Fully bio-based reprocessable thermosetting resins based on epoxidized vegetable oils cured with itaconic acid - Di Mauro, Chiara; Genua, Aratz; Mija, Alice (Industrial crops and products, 2022)
Nowadays, biomass-derived monomers production and thermosets’ recyclability are the two main efforts in the development of sustainable thermosetting epoxy resins to replace fossil derivatives and mitigate landfill build-up and ecological impact. Here, we propose a simple step and benign synthesis strategy by using the itaconic acid (IA) and two epoxidized vegetable oils (EVOs), linseed and soybean, in order to obtain fully bio-based materials with high carbon bio-content. The reactivity of these formulations, together with the properties of obtained thermosets were investigated and compared with that of DGEBA/IA homologous system. The EVOs/IA reactive mixtures show high reactivity, tested by differential scanning calorimetry (DSC) and Fourier-transformed infrared spectroscopy (FT-IR) while the obtained resins display good mechanical properties, high thermal stability as well as resistance to solvents. Due to the transesterification reaction in the polyester-based networks, recycling abilities tested both mechanically and chemically were proven. The fully reprocessed bio-based thermosets displayed almost unchanged thermomechanical properties and chemical structure combined with a simple and green chemical processing. •Benign processing of epoxidized vegetable oils formulated with itaconic acid.•Fully biobased epoxy thermosets with reprocessable properties.•High thermal, solvent stability and gel content.•A bio-based carbon content and carbon bio-content from 80% to 96.4%.